Atypical Nodular Pulmonary Kappa Light-Chain Deposition. (12th March 2021) - Nellipudi, Jessy; Brealey, John; Klebe, Sonja; Lance, David
Abstract : We report a case of an incidental positron emission tomography avid right middle lobe lesion which was increasing in size. Due to concerns regarding malignancy, the patient underwent right middle lobectomy. Microscopic examination showed a 12 × 10 × 10  mm poorly circumscribed lesion composed of eosinophilic material. The material labelled strongly for kappa light chains; however, Congo red stain was only weakly positive and without "apple-green" positive birefringence under polarised light. Electron microscopy revealed fibrillar amyloid-like material. The features were those of kappa light-chain deposition.